Nerve cells and animal behaviour - Simmons, Peter J.; Young, David (Cambridge ; New York : Cambridge University Press, 2010)
"An extensively revised third edition of this introduction to neuroethology - the neuronal basis of animal behaviour - for zoology, biology and psychology undergraduate students. The book focuses on the roles of individual nerve cells in behaviour, from simple startle responses to complex behaviours such as route learning by rats and singing by crickets and birds. It begins by examining the relationship between brains and behaviour, and showing how study of specialised behaviours reveals neuronal mechanisms that control behaviour. Information processing by nerve cells is introduced using specific examples, and the establishing roles of neurons in behaviour is described for a predator-prey interaction, toads versus cockroaches. New material includes: vision by insects, which describes sensory filtering; hunting by owls and bats, which describes sensory maps; and rhythmical movements including swimming and flying, which describes how sequences of movements are generated. Includes stunning photographs which capture the detail of the behaviour"--Provided by publisher.
"The book focuses on the roles of individual nerve cells in behaviour, from simple startle responses to complex behaviours such as route learning by rats and singing by crickets and birds. It begins by examining the relationship between brains and behaviour, and showing how study of specialised behaviours reveals neuronal mechanisms that control behaviour"--Provided by publisher.
Keywords: Neurobiology; Neurons; Animal behavior; Neurophysiology; Nervous System Physiological Phenomena; Behavior, Animal -- physiology